2016
DOI: 10.1177/1757913916676853
|View full text |Cite
|
Sign up to set email alerts
|

Arts on prescription in Scandinavia: a review of current practice and future possibilities

Abstract: The article concludes that of the Scandinavian countries, Sweden is ahead in terms of Arts on Prescription and has embraced the use of culture for health benefits on a different scale compared to Norway and Denmark. Denmark, in particular, is behind in recognising ways in which art and culture can benefit patients and for wider public health promotion. All three countries may benefit from the evidence provided by UK researchers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
58
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(60 citation statements)
references
References 28 publications
0
58
0
Order By: Relevance
“…The "prescription" is one way in which the activity is validated. Much of the focus of AoP has been on the provision of creative activities for people with mental health needs, and the evidence suggests positive benefits which include improvements in self-esteem, confidence, and mood as well as greater social contact (Bungay & Clift, 2010;Jensen, Stickley, Torrissen, & Stigmar, 2017). Furthermore, evidence finds that it is valued by referring health professionals (Stickley & Hui, 2012) and may be cost-effective (McDaid & Park, 2013).…”
mentioning
confidence: 99%
“…The "prescription" is one way in which the activity is validated. Much of the focus of AoP has been on the provision of creative activities for people with mental health needs, and the evidence suggests positive benefits which include improvements in self-esteem, confidence, and mood as well as greater social contact (Bungay & Clift, 2010;Jensen, Stickley, Torrissen, & Stigmar, 2017). Furthermore, evidence finds that it is valued by referring health professionals (Stickley & Hui, 2012) and may be cost-effective (McDaid & Park, 2013).…”
mentioning
confidence: 99%
“…However, there is a call for further studies with strong evidence to reinforce their effectiveness and economic viability and which justifies the insertion of such public programs, such as the one that occurs successfully in the United Kingdom and pointed as an example to be followed. 29 However, there is urgency in this incorporation. There are alarming data on professional exhausting, the impact on their quality of life and how much this reality compromises the quality of care provided to the population.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the White Papers reorientation to Active Care, (cultural) activities are often not part of ADL-even though it has been shown that users want more activities and that activities reduce overall costs (Conner, Young, & Silvia, 2016;Disch & Lorentzen, 2012;Haukvik & Eckhoff, 2017;Hofstad, 2018;Jensen, Stickley, Torrissen, & Stigmar, 2017;Johansen, Skaalvik Wollf, & Danielsen, 2018;Verhaeghe et al, 2014). An education programme such as Active Care appears is a way to help carers to become aware of the possibilities the cultural activities offer to achieve flourishing organizations.…”
Section: Discussionmentioning
confidence: 99%